Low Grade Lymphoma Mimicking Metastatic Urothelial Carcinoma: When Do We Need Further Histologic Staging?. (22nd November 2016) - Ali, Azka; Skelton IV, William P.; Akhavan, Neeka N.; Nguyen, Thu-Cuc; Taylor, Zachary A.; Townsend, Tabitha; Pathak, Prajwol; Hasija, Nalini; Li, Li; Indrisek, Jacqueline; Watson, Scott; Nixon, Isis; et al.
Abstract : Introduction. Patients with urothelial carcinoma of the bladder often present with metastases to regional lymph nodes, with lymphadenopathy on physical examination or radiographic imaging. Case Presentation. We present the case of a 73-year-old Caucasian man with presumed metastatic urothelial carcinoma of the bladder to regional pelvic and retroperitoneal lymph nodes. He underwent systemic chemotherapy for treatment of urothelial carcinoma and was discovered on restaging to have findings suggestive of disease progression but ultimately was found to have a concurrent secondary malignancy. Conclusion. Our case suggests that in patients with urothelial carcinoma, the concurrent presentation of regional lymphadenopathy may not be metastatic urothelial carcinoma and may warrant further investigation.